Book Review: Sedimentation in the Modern and Miocene Mahakam Delta - Dyah Tribuanawati (Berita Sedimentologi, 1999)
Sedimentation in the Modern and Miocene Mahakam DeltaBy: George P. Allen and John L. Chambers (1998), 236 p., Published by IPA (Indonesian Petroleum Association).